Adat Geunareh, Syariat Geunaseh: Building Transformative Islamic Education Based on Aceh's Local Wisdom - Muhammad Rizal; Amirul Hidayat; Mohammad Shoibul Anwar; Rodiatul Maghfiroh; Renti Yasmar; Abdul Hafiz (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
Transformative Islamic Education goes beyond the delivery of the national curriculum to include social concerns that foster personal and communal growth. This study aims to explore and analyze the role of local Acehnese values, framed in the concepts of ‘Adat Geunareh, Syariat Geunaseh’, in developing a local wisdom-based transformative Islamic education model. This research is qualitative, with an ethnographic design, conducted through in-depth interviews and participant observation in formal and non-formal Islamic educational institutions in Aceh, alongside pertinent documentation. Crucial discoveries have demonstrated an Islamic transformative education model in Acehnese society, integrating Adat and Sharia as a single interdependent value system that fortifies life in the community and in Education. Through Islamic Education, local value folklore, traditional dhikr, and khanduri, are not only sustained but also integrated into the curriculum and culture. In this model, the study identified the following features: integrated, participatory, emancipatory, and contextual-culture. The originality of this study lies in demonstrating how both formal and informal Islamic educational institutions in Aceh can effectively incorporate customary and Sharia-based local values into the national curriculum within a pluralistic society. The results highlight the importance of revising education policies to reflect local cultural characteristics and religious values better.